Metode Pembelajaran Untuk Meningkatkan Potensi Peserta Didik Melalui Pemahaman Gaya Belajar Pada Taman Kanak-Kanak Kelompok B - Karmila P. Lamadang; Anik Mufarrihah; Annisatul Iftitah; Mawaddah Mawaddah (Institut Nalanda, 2024)
Learning style is a way used by Education participants in absorbing, receiving and understanding information and stimulation given by teachers during the learning process. The purpose of this study consists of: (1) to determine the condition and learning style of Group B TK Mutiara Jaya Desa Karya Jaya, (2) to determine what are the efforts made by teachers in overcoming learning problems of students. The subjects of this study involved classroom teachers, principals and parents/guardians. The methodology in writing this thesis uses a descriptive qualitative approach, data collection through the use of observation techniques, interviews, and documentation. The results showed in 2 aspects, namely: (1) the condition and learning style of Group B TK Mutiara Jaya went quite well, the learning method that is often used in the classroom is the method of assignment. (2) efforts made by teachers in overcoming obstacles/ problems during the learning process, namely by approaching students, assessing and evaluating their students.